Penatalaksanaan Pasien Penyakit Jantung Koroner Di RSPAL dr. Ramelan Surabaya - ZULVINA, NADIFA FAULIZA; M. FATHUDDIN AL-ISLAMI; NABELLA CHOLIDATUN NIKMAH; NADHIFA NURIZZAH DHIYANISA; NADIFA SALMA SARI; ROOSTANTIA INDRAWATI; INTAN KOMALASARI (Universitas Hang Tuah, 2025)
Background: World Health Organization (WHO) data shows that coronary heart disease is the highest mortality and morbidity throughout the world among other heart and vascular diseases, namely around 43%. The pharmacological therapy is evaluated based on the rationality of drug use including the right indication, the right drug, the right patient and the right dose. The aim of evaluating rational drug use is to ensure that patients receive treatment that suits their needs and at an affordable price. The rational use of drugs is important in the success of disease and improving the quality of health. Methode: The method in research uses an observational analytical method with a retrospective cross-sectional approach, with a purposive sampling technique. Data obtained from the patient's medical record status. The population in this study were all outpatients with a diagnosis of coronary heart disease in The Polyclinic Cardiology Department at RSPAL dr. Ramelan Surabaya period of January – March 2023. Result : The most patient characteristics based on range of age were in the 56 until 65 years old, namely 113 patients (33.43%). Characteristics of patients based on gender, the highest number of coronary heart medication users were men, 240 patients (71%). Characteristics of patients based on comorbidities (with comorbidities) were mostly with comorbidities, 296 patients (88%). The percentage of rational drugs of use includes the right indication (78.70%), the right drug (82.25%), the right dose (100%), and the right patient (99.11%). Conclusion: The rationale for using coronary heart medication in coronary heart patients in the outpatient installation at RSPAL dr. Ramelan Surabaya is 94.30% rational. Keywords: Coronary Heart Disease, Evaluation of Drug Use, Drug Evaluation, Outpatient.